Do Tax Rates Encourage Profit Shifts By Multinational Companies In Indonesia - Eko Setiawan; Vera Diyanty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Due to the COVID-19 pandemic, many companies have experienced a decline in financial performance which has the potential to cause financial difficulties. While the government has provided stimulus to help, there are concerns about increasing tax avoidance efforts and profit-shifting practices with businesses transitioning to digital models. However, there is a view that companies may prefer ethical behavior to safeguard their reputation in the midst of a crisis. This study analyses profit-shifting behaviour by multinational companies in Indonesia before and during the COVID-19 pandemic, focusing primarily on the effect of differences in Indonesia's income tax rates on average rates in countries where the group of companies operates. Descriptive analysis is used in this study to provide an overview and general information about the data obtained in the field which is a research variable and will be used as analysis material to answer research questions. The research sample involved 163 companies listed on the Indonesia Stock Exchange and met certain criteria, such as the calculation of corporate income tax according to the Income Tax Law and the exclusion of certain sectors. Data was analyzed for the period 2017-2022, covering the period before and during the COVID-19 pandemic, as well as changes in tax rates in Indonesia. The results show that the difference in Indonesia's corporate income tax rate with the average tax rate in the country where multinational companies operate has a negative and significant effect on profit before tax.